2009
DOI: 10.1074/jbc.m807653200
|View full text |Cite
|
Sign up to set email alerts
|

Nicastrin Is Dispensable for γ-Secretase Protease Activity in the Presence of Specific Presenilin Mutations

Abstract: ␥-Secretase is a multisubunit membrane protein complex consisting of presenilin (PS1), nicastrin (NCT), anterior pharynx-1, and presenilin enhancer 2. To analyze the activity of familial Alzheimer disease mutants and to understand the roles of the subunits, we established a yeast transcriptional activator Gal4p system with artificial ␥-secretase substrates containing amyloid precursor protein or Notch fragments. The ␥-secretase activities were evaluated by transcriptional activation of reporter genes upon Gal4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…This result is consistent with the finding that Nct-Aph-1 interacts with PS1 CTF (25,26,40). Intriguingly, it has been shown that a point mutation at TMD9 rendered PS1 enzymatically active without binding to Nct (41). These results support our notion that the structure of TMD9 was affected by binding of the NctAph-1 subcomplex.…”
Section: Discussionsupporting
confidence: 82%
“…This result is consistent with the finding that Nct-Aph-1 interacts with PS1 CTF (25,26,40). Intriguingly, it has been shown that a point mutation at TMD9 rendered PS1 enzymatically active without binding to Nct (41). These results support our notion that the structure of TMD9 was affected by binding of the NctAph-1 subcomplex.…”
Section: Discussionsupporting
confidence: 82%
“…40 The activity and ␥-secretase dependence of the Notch1 polypeptide created by translational initiation at M1727 argues against this model and is consistent with other recent genetic studies indicating that nicastrin stabilizes ␥-secretase, but is nonessential for ␥-secretase recognition and cleavage of Notch. 41,42 Although murine T-ALL is commonly associated with 5Ј deletions in Notch1, analysis of close to 200 human T-ALLs (on Affymetrix arrays, with either 615 000 features (250K ϩ 50K arrays) or SNP 6 arrays (1.8 million features) has not revealed focal copy number variants in NOTCH1 (Dr Charles Mullighan, St Jude Children's Research Hospital, written communication, August 4, 2010). It thus appears that the relatively large deletions that are observed frequently in murine Notch1 are rare, if they occur at all, in NOTCH1 in human T-ALL, with the important caveat that additional studies are needed to exclude the presence of smaller deletions or point mutations involving the 5Ј end of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of ␥-Secretase and Substrates-To reconstitute ␥-secretase in yeast, human PS1 or PS2, NCT, Aph1a-L-HA, FLAG-Pen2, and substrates were cloned into the following vectors, as described previously (15). Briefly, PS1 or PS2 and NCT were ligated into KpnI and XbaI sites of the pBEVY-T vector (16).…”
Section: Methodsmentioning
confidence: 99%